Game Fiksi Four Ghost Stories: Fiction Game Four Ghost Stories - Sumaki, Rangga; Kaunang, Sumenge T.G.; Sugiarso, Brave (Universitas Sam Ratulangi, 2024)
Abstract — Indonesia has various mythologies about mystical ghosts, ghost stories spread among society, namely Kuntilanak, Kuyang, Sundel Bolong, and Wewe Gombel. Ghost stories that spread in society originate from the culture of the society itself which reflects the cultural values ​​of that society. With games that can be a learning medium, this research was created with the aim of helping people understand the mythology of mystical ghosts in Indonesia. This game was created using an iterative method which has 4 stages. Based on the objectives of this research, the Fiction Game Four Ghost Stories application has been produced. This game is a 3D Horror genre. The game was created using the Unity game engine. Based on research that has been carried out, there are results from a questionnaire carried out in the first stage where participants answered questions about mystical ghost knowledge before playing the game with 8% correct results, with the second stage after playing the game answering 84% correct. Based on the results of the questionnaire, the game